Indoor airflow interactions with symmetrical and asymmetrical heat load distributions under diffuse ceiling ventilation. (3rd July 2019) - Lestinen, Sami; KilpelÄinen, Simo; Kosonen, Risto; Jokisalo, Juha; Koskela, Hannu; Li, Angui; Cao, Guangyu
Abstract : Heat load distribution and supply air jets have a major effect on indoor airflow patterns, which may cause local thermal discomfort. In this study, heat load distribution was studied at the heat load strength of 40 W/floor-m 2 and 80 W/floor-m 2 with diffuse ceiling ventilation. Experimental measurements were carried out in a test chamber of 5.5 x 3.8 x 3.2 m 3 by using omnidirectional anemometers and long averaging time. Indoor air temperature of the test chamber was 26 ± 0.5 °C. In the symmetrical setup, cylindrical heat sources were located evenly on the floor. In the asymmetrical setup, two workstations were located near windows. This study recommends the reduction of buoyancy and momentum driven flows in the occupied zone. In a symmetrical setup, the local draft rate exceeded 10% in at least one height from all the measured locations and the heat load strengths in the occupied zone. In an asymmetrical setup, 47% of the measured locations exceeded 10% at 40 W/floor-m 2 and 87% at 80 W/floor-m 2, correspondingly. Thus, the thermal environment was classified as category B for 40 W/floor-m 2 and category C for 80 W/floor-m 2 according to EN ISO 7730 standard (CEN2005 ). Spatial differences increased with the asymmetrical setup compared to the symmetrical one, and those differences increased with an increase in the heat load.